Analysis of the gut contents of largehead hairtail, trichiurus lepturus (Linnaeus, 1758) in Surigao Del Sur. - Barros, Andrea Philline R. (2019.)
The traditional gut content analysis is one of the methods used which investigates feeding interactions, specifically those belonging to the aquatic food webs. The ribbonfish, Trichiurus lepturus is an economically important fish, and due to its high demand to other Southeast Asian countries especially in the Philippines, there is a targeted fishery for this resource. However, the catch of these species in the country has declined recently. Since feeding habits are fundamental to understanding the ecology of community, this study aimed to analyse the gut contents of Trichiurus lepturus. A total of 66 guts were examined in the study. The size ranged from 101-505 mm in total length. The fed mostly on fished including Encrasicholina sp., and shrimps such as Acetes, Penaeus, and Lucifer. Moreover, there was an occurrence of cannibalism but only larger individuals. Microplastics were also evident in most of the size classes.
Special Problem (Undergraduate, Bachelor of Science in Biology ) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2019.
Keywords: Largehead hairtail -- Surigao del Sur; Trichiurus lepturus